Influencing the mind of the consumers: the role of the law and the regulators in controlling credit advertisement - Hassan, Rusni; Kassim, Salina; Abu Bakar, Elistina; Ilias, Ibtisam @ Ilyana (2018)
Advertising boosts market performance by offering useful information to consumers. It enables firms to promote the attributes of their products and services and, thereby, to compete better with each other. On the other hand, advertising may adversely affect market performance when businesses use it to transmit deceptive or fraudulent messages on which reasonable consumers are induced to rely to their detriment. Regulatory intervention is prerequisite to circumvent those promotional efforts by firms that convey untruthful and misleading information to consumers. This study examines the principal laws and regulators involved in governing consumer credit advertisement in Malaysia. The scope is limited to four major areas namely banking, hire-purchase, moneylending and pawnbroking. The piecemeal approach in regulating this industry results in different provisions are in place to regulate consumer credit advertisement by different regulators. As a consequence, prospective consumers of various credit products are subject to different levels of protection which may be greater or lower than the other. Thus, some of them may become the victim of unethical and profit-oriented credit providers who unfairly enticing consumers to close the deal relying on misleading advertisement. The study also finds that the present advertisement regime is still incomprehensive to provide adequate protection to consumers. This study proposes some recommendations to enhance the existing state of credit advertisement control. Other than ensuring inclusive and equal protection to wide range of consumers, strengthened consumer protection regime guarantee market confidence and financial stability.